Clinical features and risk factors of left ventricular hypertrophy in children with primary hypertension - Liu, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2023)
Objective: To assess the clinical features and relative factors of left ventricular hypertrophy (LVH) in children with primary hypertension. Methods: In this retrospective cohort study, 430 children diagnosed with primary hypertension in Children's Hospital, Capital Institute of Pediatrics from January 2019 to September 2022 were enrolled. Their clinical data was analyzed and LVH was assessed by echocardiography. According to left ventricular geometry, these children were assigned to the LVH group and normal geometry group. General conditions, laboratory indicators and ambulatory blood pressure parameters between two groups were compared by independent sample t-test or Mann-Whitney U test. Spearman correlation coefficient was used to analyze the correlation between LVH and clinical indicators including blood pressure, biochemical and metabolic indicators. The independent risk factors of LVH were analyzed by multivariable logistic regression. The receiver operating characteristic (ROC) curve was used to explore the value of risk factors in the diagnosis of LVH. Results: Among the 430 children with primary hypertension, 342 (79.5%) were males and 88 (20.5%) females. Their age was (12.6±2.3) years, and 123 children (28.6%) of them had LVH. Body mass index (BMI) ((30.0±5.2) vs. (26.2±4.3) kg/m2), ratio of stage 2 hypertension (75.6% (93/123) vs. 59.6% (183/307)), 24-hour systolic blood pressure (24 h SBP)((131±10) vs. (128±10) mmHg,1 mmHg=0.133 kPa), daytime systolic blood pressure (SBP) ((135±11) vs. (131±11) mmHg), nighttime SBP ((128±11) vs. (123±10) mmHg), cholesterol level ((4.0±0.7) vs. (3.9±0.7) mmol/L), serum uric acid level ((447±81) vs. (426±91) μmol/L) and incidence of hyperinsulinemia (69.9% (86/123) vs.59.0% (181/307)) were significantly elevated in the LVH group compared with those in the normal geometry group (all P<0.05). There were more patients with a disease course over 5 years in the LVH group than in the normal geometry group, with a statistically significant difference (χ2=8.90,P=0.031). Spearman correlation analysis showed that BMI, 24 h SBP, daytime SBP, nighttime SBP, triglyceride, uric acid, and serum sodium level were positively correlated with LVMI (r=0.43, 0.20, 0.18, 0.18, 0.18, 0.16, and 0.12, all P<0.05). BMI, hyperinsulinemia, and cholesterol level were positively correlated with relative wall thickness (RWT) (r=0.22, 0.12, and 0.16, all P<0.05). The multivariate logistic regression analysis showed that BMI (OR=1.17, 95%CI 1.10-1.25) and 24 h SBP (OR=1.04, 95%CI 1.01-1.08) were the independent risk factors for LVH (both P<0.05). The area under the receiver operator characteristic curve, combined with BMI and 24 h SBP, was 0.72 (95%CI 0.67-0.77, P<0.05), with a sensitivity and specificity of 71.5% and 64.8%, respectively. Conclusions: BMI and 24 h SBP are the independent risk factors for LVH in children with primary hypertension, and the combination of BMI and 24 h SBP has an acceptable diagnostic value for LVH. Early monitoring of these indexes is necessary to predict preclinical cardiac damage